2008
DOI: 10.1007/s11162-008-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Psychosocial Dispositions, and the Academic Achievement of College Students

Abstract: Researchers have recently claimed that there are substantial differences in the psychosocial dispositions and academic achievement of male and female college students. To test this proposition, a sample of 854 undergraduate students were selected from a major Canadian Research-1 university. Multiple regression analyses assessed the effects of gender and several other independent variables on coping strategies, academic control, self-esteem, and grade point averages. Few differences emerged between the genders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
0
22
1
2
Order By: Relevance
“…Predictors of academic achievements were discovered to vary also according to gender, just as in the Canadian study (Clifton et al, 2008). The strategies most frequently used by male students were positive correlates and predictors of academic achievement, while in the case of women, strategies that correlated with average grades ranked slightly lower in their hierarchy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Predictors of academic achievements were discovered to vary also according to gender, just as in the Canadian study (Clifton et al, 2008). The strategies most frequently used by male students were positive correlates and predictors of academic achievement, while in the case of women, strategies that correlated with average grades ranked slightly lower in their hierarchy.…”
Section: Discussionmentioning
confidence: 81%
“…It should be assumed that other factors are more significant. A Canadian study emphasized the importance of having a sense of control over one's academic achievements (Clifton, Perry, Roberts, & Peter, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Wintre and Yaffe (2000) found that fathers' level of education was a predictor for males' first year GPA, whereas mothers' level of education was a significant predictor for females' first year GPA. Clifton et al (2007) contend that highly educated parents are more capable of providing their children with social and financial support for their post-secondary education. Given that tuition costs and financial barriers seem to be rising for undergraduate students (Statistics Canada 2008), it seems appropriate to investigate parents' education levels and socio-economic status as predictors of academic success.…”
Section: Demographic and Familial Variablesmentioning
confidence: 99%
“…A warm and caring environment where the teacher is seen as part of "the team" and maintains high expectations is thought to be best (Clifton & Roberts, 1988;Stairs, 1991;Watt-Cloutier, 2000) and is something teachers can work towards. Finally, engagement and respect will be noticed by students, parents, and community members.…”
Section: Caring Engagement and Respectmentioning
confidence: 99%